2001
DOI: 10.1074/jbc.m105303200
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II Elongator Holoenzyme Is Composed of Two Discrete Subcomplexes

Abstract: Elongator is a histone acetyltransferase complex that associates with the elongating form of RNA polymerase II. We purified Elongator to virtual homogeneity via a rapid three-step procedure based largely on affinity chromatography. The purified factor, holo-Elongator, is a labile six-subunit factor composed of two discrete subcomplexes: one comprised of the previously identified Elp1, Elp2, and Elp3 proteins and another comprised of three novel polypeptides, termed Elp4, Elp5, and Elp6. Disruption of the yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
194
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(201 citation statements)
references
References 26 publications
6
194
1
Order By: Relevance
“…The purified Elp123 sample (Fig 2A) was stabilized with low amounts of glutaraldehyde and eluted from a gel filtration column at a volume expected for a ~610 kDa complex. This suggested that the Elp123 sub‐complex in isolation also harbors two copies of each of the three subunits, as previously described for the full complex 20, 28.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The purified Elp123 sample (Fig 2A) was stabilized with low amounts of glutaraldehyde and eluted from a gel filtration column at a volume expected for a ~610 kDa complex. This suggested that the Elp123 sub‐complex in isolation also harbors two copies of each of the three subunits, as previously described for the full complex 20, 28.…”
Section: Resultssupporting
confidence: 74%
“…We constructed yeast strains carrying endogenously TAP‐tagged versions of Elp1 and Elp6 and purified Elongator using previously established purification protocols 20. Consistent with sub‐stoichiometric cellular amounts of Elp456 in vivo 28, 36, 37, purifications of Elp1‐TAP resulted in an excess of Elp123 sub‐complex 20, whereas Elp6‐TAP purifications resulted in reduced quantities but yielded highly pure, complete, and stoichiometric Elongator complex. Large‐scale preparations yielded sufficient amounts of pure Elongator complex and Elp123 sub‐complex to analyze their overall architecture and shape by EM.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although we do not have antibody to endogenous D-elp1, S2 cells expressing V5-tagged D-elp1 and a GFP marker selectively lost D-elp1 expression when knocked down in parallel cultures, suggesting the endogenous protein was also depleted under the treatment conditions used. D-elp1 is the largest of the three subunits in the core elongator complex, and D-elp3 has been shown to have histone acetyl transferase activity that facilitates pol II transcription through chromatinized templates in vitro (16,23,24). We wanted to know if D-elp1 depletion alone was responsible for the effects on RNA silencing or if the three subunits of the core elongator complex were equally involved, suggesting a role for the elongator complex itself.…”
Section: D-elp1 Interacts With Dcr-2 and Is Involved In Rnaimentioning
confidence: 99%
“…100 Little is known about how Elp1 functions in disease-relevant sympathetic and sensory neurons because most studies have focused on nonneuronal cells from FD patients (eg, fibroblasts and leukocytes) or they have involved Elp1 protein modulation in cells not normally involved in disease. 101e106 Elp1 is a constituent of the heterohexameric transcriptional elongator complex 107 ; therefore, it may be involved in transcriptional regulation. 102,103,108 Interestingly, however, a significant amount of Elp1 protein is found in a vesicular pattern in the cytoplasm of both nonneuronal cells 104,109 and neurons ( Figure 1B), suggesting that it has a function apart from transcription.…”
Section: Fd: a Model Of Abnormal Retrograde Ngf Signaling Resulting Imentioning
confidence: 99%